2005
DOI: 10.1105/tpc.105.034876
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Response Factors MediateArabidopsisOrgan Asymmetry via Modulation of KANADI Activity

Abstract: Members of the KANADI gene family in Arabidopsis thaliana regulate abaxial identity and laminar growth of lateral organs. Promoter APETALA3-mediated ectopic expression of KANADI restricts petal expansion and was used in a genetic screen for factors involved in KANADI-mediated signaling. Through this screen, mutations in ETTIN (ETT; also known as Auxin Response Factor3 [ARF3]) were isolated as second site suppressors and found to ameliorate ectopic KANADI activity throughout the plant as well. Mutant phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
477
0
22

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(517 citation statements)
references
References 60 publications
18
477
0
22
Order By: Relevance
“…ett arf4 double mutants have several lateral organ defects, such as short sepals with abaxial protrusions, narrow petals, sterile stamens, and gynoecia with distal abaxial and adaxial ovules, thus showing that these genes act in concert. Interestingly, these phenotypes are also seen in kan1 kan2 double mutants (Pekker et al, 2005). Recently, physical interactions between KANADI4 (KAN4/ ATS) and ETTIN were shown to coordinate ovule and integument development (Kelley et al, 2012).…”
Section: Regulation Of Kanadi and Ettin Genes Contributes To Organ Dementioning
confidence: 93%
“…ett arf4 double mutants have several lateral organ defects, such as short sepals with abaxial protrusions, narrow petals, sterile stamens, and gynoecia with distal abaxial and adaxial ovules, thus showing that these genes act in concert. Interestingly, these phenotypes are also seen in kan1 kan2 double mutants (Pekker et al, 2005). Recently, physical interactions between KANADI4 (KAN4/ ATS) and ETTIN were shown to coordinate ovule and integument development (Kelley et al, 2012).…”
Section: Regulation Of Kanadi and Ettin Genes Contributes To Organ Dementioning
confidence: 93%
“…1C). Auxin response factors ARF3 and ARF4 are known to regulate a subset of the traits associated with the vegetative-toreproductive transition and leaf heteroblasty (Pekker et al, 2005). It has also been reported that the production of tasiR-ARF, a trans-acting siRNA that targets both ARF3 and ARF4, requires P-labeled full-length GFP cDNA probe.…”
Section: Discussionmentioning
confidence: 99%
“…Strong ett/arf3 mutations simplify the shape of spongy mesophyll cells in a manner similar to that of kan1, and ett/arf3 arf4 double mutants resemble kan1 kan2 double mutants. Furthermore, ett/arf3 is able to suppress the floral phenotype of KAN1 overexpression (Pekker et al 2005). Because many of the traits that change during vegetative development are polarized (e.g., trichome production and leaf curvature), it may be that temporal changes in the regulation of leaf polarity are the basis for the phase-specific expression pattern of these traits.…”
Section: Biogenesis Of Ta-sirnasmentioning
confidence: 99%
“…Mutations in ETT/ARF3 were originally identified because of their effects on carpel polarity (Sessions and Zambryski 1995;Sessions et al 1997). Subsequent studies showed that ETT/ARF3 and ARF4 regulate leaf polarity as well, probably in conjunction with the KAN family of transcription factors (Pekker et al 2005;Hunter et al 2006). Strong ett/arf3 mutations simplify the shape of spongy mesophyll cells in a manner similar to that of kan1, and ett/arf3 arf4 double mutants resemble kan1 kan2 double mutants.…”
Section: Biogenesis Of Ta-sirnasmentioning
confidence: 99%